2018
DOI: 10.3390/beverages4020045
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Juice Press Fractions for Sparkling Base Wines by a UV-Vis Spectral Phenolic Fingerprint and Chemometrics

Abstract: The feasibility of an ultraviolet-visible (UV-Vis) spectral phenolic fingerprint (SPF), combined with principal component analysis (PCA), is evaluated as a rapid, simple, and reliable technique for the discrimination of grape juice press fractions destined for the production of sparkling white wines. Juice press fractions of Vitis vinifera L. Chardonnay and Pinot noir grapes comprising free-run (i.e., juice released during the loading of press), cuvée (i.e., first press fraction), and taille (i.e., subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Juice samples were clarified by centrifugation, diluted 1/50 in 1 M HCl, using disposable quartz cuvettes and the samples were individually scanned between the wavelengths 200-600 nm with a spectrophotometer (SPECTROstar Nano , BMG LABTECH, Windsor, NSW, Australia) to collect phenolic spectral fingerprints [28]. Total phenolics were calculated using absorbance at 280 nm and measured in absorbance units (AU) [17,20]. A recent study using this method with apple cider showed peaks occurring at 280 nm, indicating total phenolics, as results have found in similar studies measuring the total phenolic content in wine [2,17,29].…”
Section: Juice Quality Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Juice samples were clarified by centrifugation, diluted 1/50 in 1 M HCl, using disposable quartz cuvettes and the samples were individually scanned between the wavelengths 200-600 nm with a spectrophotometer (SPECTROstar Nano , BMG LABTECH, Windsor, NSW, Australia) to collect phenolic spectral fingerprints [28]. Total phenolics were calculated using absorbance at 280 nm and measured in absorbance units (AU) [17,20]. A recent study using this method with apple cider showed peaks occurring at 280 nm, indicating total phenolics, as results have found in similar studies measuring the total phenolic content in wine [2,17,29].…”
Section: Juice Quality Analysismentioning
confidence: 99%
“…Traditionally cider makers have utilised the Folin-Ciocalteu method [16] to determine the total phenolic content of the apple juice, however a simpler method has been developed for the wine industry which utilises a simple dilution and UV-vis spectrometry which provides a spectral phenolic fingerprint [17]. The sample's absorbance is measured at 280 nm wavelength and recorded in absorbance units (AU) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, spectroscopy techniques have been used to evaluate and monitor the origin and the integrity of different alcoholic beverages, including whisky [2,[7][8][9][10][11][12][13][14][15][16]. Due to the variety of origins and raw materials used, whisky is often subjected to adulteration [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of spectrophotometric techniques is of interest to the alcoholic beverage industries, since most laboratories are equipped with cheap and easy to use UV-VIS spectrophotometers [2,7]. UV-VIS spectroscopy relies on π bonding and conjugated double bonds, where phenolic compounds have distinct UV fingerprints, while the most abundant sample components, such as water, alcohol, organic acids, and sugars, have no absorbance in the UV wavelength region (200-600 nm) [2,7,15,17]. Recently, analytical methods based in UV-VIS spectroscopy have been reported as having a great potential to target issues related with brand authentication and traceability in a diverse group of distilled spirits, such as whisky, brandy, rum, and other flavoured spirits [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation